2019
DOI: 10.1364/boe.10.001935
|View full text |Cite
|
Sign up to set email alerts
|

Efficient nanoheater operated in a biological window for photo-hyperthermia therapy

Abstract: Remotely monitoring and regulating temperature in a small area are of vital importance for hyperthermia therapy. Herein, we report ~11 nm NaErF 4 nanocrystal as the ultra-small nanoheater, which is highly safe for biological applications. Under 1530 nm photon excitation, upconversion intensity of NaErF 4 is significantly enhanced as compared to the conventionally used 980 nm pumping source. Upconversion mechanisms are discussed on the basis of power dependence measurements. Importantly, light-to-heat transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 35 publications
(45 reference statements)
0
5
0
Order By: Relevance
“…But until recently, Ln nanomaterials, typically Nd 3+ :LnF 3 , have been introduced in the organisms as PTT probes, first serving for the temperature feedback , and then for both temperature feedback and heating. In addition, to enhance the energy harvest of the probes, high doping nanomaterials such as NaErF 4 , NdVO 4 , and Nd 3+ enriched α-NaYF 4 nanocrystals were very recently proposed. Unfortunately, current Ln probes are still facing difficulties for PTT application. For instance, Nd 3+ :LnF 3 has a larger particle size basically >15 nm (Table S1) and relatively low heat generation due to limited doping concentration; NdVO 4 yields extremely weak light, and thus the problem is lack of temperature feedback.…”
Section: Introductionmentioning
confidence: 99%
“…But until recently, Ln nanomaterials, typically Nd 3+ :LnF 3 , have been introduced in the organisms as PTT probes, first serving for the temperature feedback , and then for both temperature feedback and heating. In addition, to enhance the energy harvest of the probes, high doping nanomaterials such as NaErF 4 , NdVO 4 , and Nd 3+ enriched α-NaYF 4 nanocrystals were very recently proposed. Unfortunately, current Ln probes are still facing difficulties for PTT application. For instance, Nd 3+ :LnF 3 has a larger particle size basically >15 nm (Table S1) and relatively low heat generation due to limited doping concentration; NdVO 4 yields extremely weak light, and thus the problem is lack of temperature feedback.…”
Section: Introductionmentioning
confidence: 99%
“…The photothermal effects of the laser irradiation on the LaOF:Yb 3+ , Er 3+ UCNPs were investigated by determining their heat efficiency under the 980 nm laser with a power density of 6.91 W/cm 2 . The steps employed for the determination of the photothermal conversion efficiency (η) is described in the Supporting Information. The light-to-heat conversion efficiency was found to be 11.92% for the LaOF:Yb 3+ , Er 3+ UCNPs. From the perspective of luminescence thermometry, this value of photothermal conversion efficiency is acceptable and would not produce any significant alteration in the thermal readouts.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, higher the values of the thread setting density, linear density, weight per square meter (GSM), and tensile properties better will be the performance and quality of textile products [38,39]. The recycled textile and composites materials have reasonable applications in optical sensing, automobiles and medical industries [40,41]. Based on literature and experimental results, it can be concluded that relative sliding COF value between textile waste and metallic components during shredding, cutting, and recycling should be greater than 0.25 due to damage, rough, and the distorted surface of textile fabrics.…”
Section: Resultsmentioning
confidence: 99%